ANALYSIS OF TEACHER DIFFICULTIES IN COMPILING TEACHING MODULES BASED ON THE INDEPENDENT LEARNING CURRICULUM - Nur Rahmah; Andini Puteri; Lale Novi Laela Purnama; Arya Abdul Bari; Haifaturrahmah (Universitas Islam Negeri Mataram, 2024)
The implementation of an independent curriculum in schools is closely related to the teacher's ability to compile teaching modules. Teachers are required to have the skills to structure teaching modules effectively. This study aims to answer the formulation of the problem about the Analysis of Teacher Difficulties in Compiling Teaching Modules Based on the Independent Learning Curriculum at SDN 2 Cakranegara Mataram City. This study used a descriptive qualitative approach. Based on the results of the study, various difficulties faced by teachers were found when compiling teaching modules. There are three difficulty criteria identified in this study, namely: (1) as many as 35% of teachers understand teaching modules and their components; (2) as many as 15% of teachers understand the teaching module but do not understand its components, and (3) as many as 50% of teachers do not understand teaching modules and their components. Faced with conditions like this, every teacher who has difficulty understanding teaching modules is the responsibility of the school to provide guidance and assistance, because the quality of teachers has a significant impact on the implementation of the independent learning curriculum.